Towards of an information service to educational leaderships : business intelligence as analytical engine of service - Ferreira, Andreia (2014)
The use of Information Technologies (IT) in educational sector is diverse. However in pedagogical area and administrative to the undergraduate education (UE) it is inadequate and cannot be used to monitoring the education and school performance. Generally these public institutions have some difficulties in performing regularly and mandatory performance evaluation, addressing three governance facets. Schools are the kernel of educational politics and to evaluate them there is a mandatory two-way process: an assessment program from school responsibility and a ministerial assessment program carry on by the inspectorate. The homemade assessment gives to the school a total independence. The Institutional and inspectorate assessment program covers three domains: •Academic results •Educational service provision •Leadership and management Each domain has several topics and indicators. The indicators are normally manually calculated using datasheets. In order to innovate and improve this process was introduced the Business Intelligence (BI) concepts as a service. In this case the BI has as main goal to help the schools to make smart decisions and obtain new indicators through data and information collected by the various information systems. This papers presents the first phase of the process, addressing the design of a pervasive BI architecture to ensure the service value and sustainability making them universal.